Ralph Cook Square at the corner of Charles and Mount Vernon Streets, January 14, 1973 - Waid, C. Franklin (Tufts Archival Research Center, 2005)
Street-level view northeast of Ralph Cook Square, located on the northeast corner of Charles and Mount Vernon Streets. Signage adorns the facade of 63 Charles Street, which faces west. Commercial products are displayed in the storefront windows of the building. A traffic light, street lamps and parking meters line the sidewalk along the east side of Charles Street. Houses located on the north side of Mount Vernon Street are located to the east of 63 Charles Street. Automobiles parked along the east side of Charles Street and north side of Mount Vernon Street are included in the photograph. 7 3/8 x 9 3/8, 7 7/8 x 9 7/8 overall Photographs